Measuring at home - Roy, Jennifer Rozines, 1967- (Roy, Jennifer Rozines, 1967- Math all around., 2007)
"Introduces the concept of measuring to record height, weight, volume, time, and temperature, including the use of measuring tools. Stimulates critical thinking and provides students with an understanding of math in the real world"--Provided by publisher.